(untitled) (The Pakistan Development Review, 1996)
Iftikhar H. Malik has taken on a daunting task in trying to write on the state and society of Pakistan. He examines the “triangle of authority, ideology, and ethnicity” and attempts to provide a theoretical and historical framework for the study of Pakistan’s chequered political history. Much in view is the role of the important ruling classes and groups, including the military, the bureaucracy, and the feudals, in the state formation of Pakistan. The author then goes on to discuss the problems of national integration, ethnicity, gender, and the role of the intelligence agencies. The book has obviously required and is based on a great deal of research involving both primary and secondary sources. Wide reference and erudition are fully in evidence.